THE DEVELOPMENT OF INCH'S CRITICAL THINKING MULTIPLE CHOICE TEST ON SENSE TOPIC AND IT'S APPLICATION TO EXAMINE THE PROFILE IN JUNIOR HIGH SCHOOL STUDENTS - Amalia, Citra (2015)
This study with title "The Development of Inch's Critical Thinking Multiple Choice Test on Sense Topic and It's Application to Examine The Profile in Junior High School Students" has a purpose to develop a test to measure critical thinking and describe the profile of students' critical thinking on sense topic in private junior high school. The background of this research is the thinking of importantance of test instrument development to measure and profiling critical thinking. Because it is viewed as one aspect of the 21st Century skill as one of thinking skill that include in curriculum by most of country in the world. Therefore, especially in Indonesia, the research regarding critical thinking is needed to compete in global's education. The method that was used in this research was descriptive. The sample was taken 20 students from 8th grade of three private junior high school. The test is 20 question choosen fulfill eight indicator of Inch's critical thinking. The result of the test analysed by ANATES ver 4.0.9 show r= 0.8 and IBM SPSS Statistic 20 software show α= 0.802. Another analysis has been made from expert judgement and interview with teacher. These result meant that the test is feasible to measure students' critical thinking. Based on the result of the research in profiling three private secondary school, it is shown that average students' critical thinking shown 51.8% which categorized as 'prosperous'. This result show that the level of inch's critical thinking in private junior high school show as prosperous and need to be improve. ----------Penelitian ini diberikan judul "The Development of Inch's Critical Thinking Multiple Choice Test on Sense Topic and It's Application to Examine The Profile in Junior High School Students" memiliki tujuan untuk mengembangkan tes untuk mengukur berpikir kritis dan menggambarkan profil dari berpikir kritis siswa pada topik alat indera di sekolah swasta setingkat SMP. Latar belakang penelitian ini adalah pemikiran dari pentingnya pengembangan instrumen tes untuk mengukur dan mengetahui profil berpikir kritis. Karena dipandang sebagai salah satu aspek dari keterampilan abad ke-21 sebagai salah satu keterampilan yang tercakup dalam kurikulum oleh sebagian besar negara di dunia. Oleh karena itu, terutama di Indonesia, penelitian mengenai berpikir kritis diperlukan untuk bersaing dalam pendidikan global. Metode yang digunakan dalam penelitian ini adalah deskriptif. Sampel diambil 20 siswa dari kelas 8 tiga sekolah swasta setingkat SMP. Tes ini terdiri atas 20 pertanyaan yang dipilih memenuhi delapan indikator berpikir kritis Inch ini. Hasil tes dianalisis dengan ANATES ver 4.0.9 r = 0,8 dan IBM SPSS Statistik 20 software α = 0,802. Analisis lain telah dibuat dari expert judgement dan wawancara dengan guru. Hasil ini berarti bahwa tes tersebut layak untuk mengukur berpikir kritis siswa. Berdasarkan hasil penelitian di profil tiga sekolah menengah swasta, terlihat bahwa siswa rata-rata 'berpikir kritis yang ditunjukkan 51,8% yang dikategorikan sebagai ' cukup '. Hasil ini menunjukkan bahwa tingkat berpikir kritis inch di sekolah menengah pertama swasta adalah pada tingkatan cukup dan perlu meningkatkan.